A phase 1 study to evaluate the safety and pharmacokinetics of MEDI8852, an anti-influenza A monoclonal antibody, in healthy adult volunteers. (November 2017) - Mallory, Raburn M.; Ali, S.Omar; Takas, Therese; Kankam, Martin; Dubovsky, Filip; Tseng, Leo
Abstract: MEDI8852 is an IgG1 kappa monoclonal antibody that is being developed to treat patients hospitalized with influenza A. We evaluated the safety and tolerability, pharmacokinetics, and anti-drug antibodies (ADA) of a single intravenous dose of MEDI8852 in healthy adult volunteers (NCT02350751 ). Forty subjects were randomized to receive either MEDI8852 (250, 750, 1, 500, or 3000 mg) ( n  = 32) or placebo ( n  = 8) on day 1. Dose escalation was based on cumulative safety data through day 8. Subjects were followed through day 101 for safety, pharmacokinetics, and ADA. Treatment-emergent adverse events (TEAEs) were comparable (37.5%; 37.5%); all TEAEs were mild (grade 1) or moderate (grade 2) in severity. The most frequently reported TEAEs were headache (9.4%, 12.5%) and hypoglycemia (12.5%, 12.5%); all subjects with hypoglycemia were asymptomatic and did not require treatment. No subjects discontinued the study due to a TEAE. Mean area under the curve from time 0 to last sampling time point, area under the curve from time 0 to infinity, and observed maximum concentration for MEDI8852 were dose proportional. The terminal half-life ranged from 19.4 to 22.6 days. No ADAs were detected. A population pharmacokinetic model demonstrated good concentration separation between the 750- and 3000-mg dose groups.